Immunohistochemical, pharmacovigilance, and omics analyses reveal the involvement of ATP-sensitive K+ channel subunits in cancers: role in drug–disease interactions - Maqoud, Fatima; Zizzo, Nicola; Attimonelli, Marcella; Tinelli, Antonella; Passantino, Giuseppe; Antonacci, Marina; Ranieri, Girolamo; Tricarico, Domenico (Frontiers in Pharmacology, 2023)
Background: ATP-sensitive-K+ channels (KATP) are involved in diseases, but their role in can-cer is poorly described. Pituitary macroadenoma has been observed in Cantu’ syndrome (C.S.), which is associated with the gain of function mutations of the ABCC9 and KCNJ8 genes. We tested the role of the ABCC8/Sur1, ABCC9/Sur2A/B, KCNJ11/Kir6.2, and KCNJ8/Kir6.1 genes ex-perimentally in a minoxidil-induced renal tumor in male rats and in the female canine breast cancer a spontaneous animal model of disease, and in the pPharmacovigilance and oOmics da-tabases. Methods: We performed biopsies from renal tissues of male rats (N=55) following a sub-chronic high dosing topical administration of minoxidil (0.777-77.7 mg/kg/day), and from breast tissues of female dogs for diagnosis (N=23), that were analyzed by immunohistochemistry. Pharma-covigilance and oOmics data were extracted from EudraVigilance and oOmics databases, respec-tively. Results: An elevated immunohistochemical reactivity to the Sur2A-mAb was as beenwas detect-ed in the cytosol of the Ki67+/G3 cells other than in the surface membrane in the minoxidil-induced renal tumor and the breast tumor samples. KCNJ11, KCNJ8, and ABCC9 genes are up-regulated in cancers but the ABCC8 is down-regulated. The Kir6.2-Sur2A/B-channel opener minoxidil showed 23 case reports of breast cancer and 1 case of ovarian cancer in line with oOm-ics data reporting, respectively, the negative and positive prognostic roles of the ABCC9 gene in these cancers. Sulfonylureas and glinides blocking the pancreatic Kir6.2-Sur1 subunits showed a higher risk for pancreatic cancer in line with the positive prognostic role of the ABCC8 gene but low risks for common cancers. GlibencMlamide, repaglinide, and glimepiride show a lower can-cer risk within the KATP channel blockers. The Kir6.2-Sur1 opener diazoxide shows no cancer reactions. Conclusion: An elevated expression of the Sur2A subunit waswas found in proliferating cells in two animal models of cancer. Immunohistochemistry/oOmics/pharmacovigilance data reveal the role of the Kir6.1/2-Sur2A/B subunits as a drug target in breast/renal cancers and in C.S..